# Been trying to figure this one out for some time

LogeX=2loge(100-y^2)+C where X(0)=100 find C.
i keep getting different ans, dunno where i am going wrong

HallsofIvy
Homework Helper
We can't tell you what you are doing wrong if you don't tell us what you are doing!

Also, what do you mean by X(0)? Are you thinking of X as a function of y? That is, X(0)= 100 means that if y= 0, X= 100?

LogeX=2loge(100-y^2)+C where X(0)=100 find C.
i keep getting different ans, dunno where i am going wrong

Assuming this equation is more correctly written as:
Log(e^X) = 2 * Log[e^(100-Y^2)] + C

and, assuming
... what do you mean by X(0)? Are you thinking of X as a function of y? That is, X(0)= 100 means that if y= 0, X= 100?

then we have:
Log(e^100) = 2 * Log(e^100) + C
and C = -Log(e^100)

But, if you really mean to use natural log (Ln), rather than the base 10 logarithm (Log), the equation becomes:
Ln(e^100) = 2 * Ln(e^100) + C

and, since Ln(e^x) = x, we have:
100 = 2 * 100 + C
100 = 200 + C
C = -100

HallsofIvy
Homework Helper
I assumed that he does not mean log(ex) but that "Loge" meant "log base e" or natural logarithm.

Hopefully, imperiale will come back and explain in more detail exactly what he is trying to do.

I assumed that he does not mean log(ex) but that "Loge" meant "log base e" or natural logarithm.

If this is the case, then using Log base e (better known as natural logarithm, or "Ln"), the equation becomes:
Ln(X) = 2 * Ln(100 - Y^2) + C

and, still assuming
... what do you mean by X(0)? Are you thinking of X as a function of y? That is, X(0)= 100 means that if y= 0, X= 100?

we would have:
Ln(100) = 2 * Ln(100) + C
and C = -Ln(100)